2020
DOI: 10.1167/iovs.61.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Regulation of IOP Rhythm by Dual Pathways of Glucocorticoids and the Sympathetic Nervous System

Abstract: PURPOSE. Elevated IOP can cause the development of glaucoma. The circadian rhythm of IOP depends on the dynamics of the aqueous humor and is synchronized with the circadian rhythm pacemaker, that is, the suprachiasmatic nucleus. The suprachiasmatic nucleus resets peripheral clocks via sympathetic nerves or adrenal glucocorticoids. However, the detailed mechanisms underlying IOP rhythmicity remain unclear. The purpose of this study was to verify this regulatory pathway. METHODS. Adrenalectomy and/or superior ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…This regulatory pathway is consistent with β1-AR-mediated circadian regulation of the pineal gland 58 . In our previous report, NE instillation generated a transient IOP increase within 1 day, but not the day after instillation 19 . It may be possible to partly explain not only the AH production rhythm, but also the NEmediated driven-out rhythm of AH out ow resistance.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This regulatory pathway is consistent with β1-AR-mediated circadian regulation of the pineal gland 58 . In our previous report, NE instillation generated a transient IOP increase within 1 day, but not the day after instillation 19 . It may be possible to partly explain not only the AH production rhythm, but also the NEmediated driven-out rhythm of AH out ow resistance.…”
Section: Discussionmentioning
confidence: 67%
“…Drug instillation was performed as described in our previous report 19 . Unanesthetized 8-week old male mice were used in this study.…”
Section: Drug Instillationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, sympathetic nerve activity increases with an increase in core temperature in response to acute heat stress (Niimi et al 1997). Norepinephrine released by the sympathetic nerve could be involved in mediating IOP rhythm (Ikegami et al 2020). As the lens thickness increases with age, the lens is thicker in elderly individuals than in younger individuals (Zeng et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To rule out the possibility that this altered behavior was caused by stress or anxiety, we measured stress hormones and neurotransmitters in the serum and brain during the day phase of LD. Corticosterone and norepinephrine release are regulated by stress and the circadian clock [Le Minh et al, 2001;Ikegami et al, 2020]. In Ud6-m-/p+ mice, we found that serum corticosterone levels are lower at ZT10-12 (Fig.…”
Section: Reduced Stress Hormones and Anxiety In Ud6-m-/p+ Micementioning
confidence: 95%